(untitled) (Scientific journal of the Fergana State University, 2025)
Abstract: News headlines are pivotal in capturing reader attention and shaping initial perceptions in a digital age marked by rapid information consumption. This study investigates the role of grammatical compression in optimizing news headlines, focusing on how various strategies impact audience engagement and comprehension. Grammatical compression, involving the deliberate omission of linguistic elements to achieve brevity, enhances attention-grabbing potential but may compromise clarity. Utilizing a mixed-methods approach, this research combines quantitative content analysis and qualitative discourse analysis to evaluate the prevalence and effects of different compression strategies. Findings reveal a trade-off between brevity and readability, with compressed headlines often exhibiting lower clarity and increased cognitive load. The study underscores the importance of balancing compression with clarity to maximize both engagement and comprehension, offering insights into optimizing headline construction in the evolving digital media landscape.